1968
DOI: 10.1149/1.2410973
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Properties of Nb[sub 2]O[sub 5] Thin Film Capacitors

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Niobium oxides have widely varying properties depending upon the exact stoichiometric ratio, crystal structure and test conditions [34]. For illustration, a 5 nm thick layer of Ni 2 O 5 with a relative permittivity,    41 0 , and a room-temperature loss tangent, q  tan 0.01 is considered here [41,42]. Again from equations (23) and (24) the expected PSD 50 μm above the surface at 1 MHz is around´-1.5 10 12 V 2 m −2 Hz −1 parallel to the surface and 3×10 −12 V 2 m −2 Hz −1 normal to the surface.…”
Section: Native Oxidesmentioning
confidence: 99%
“…Niobium oxides have widely varying properties depending upon the exact stoichiometric ratio, crystal structure and test conditions [34]. For illustration, a 5 nm thick layer of Ni 2 O 5 with a relative permittivity,    41 0 , and a room-temperature loss tangent, q  tan 0.01 is considered here [41,42]. Again from equations (23) and (24) the expected PSD 50 μm above the surface at 1 MHz is around´-1.5 10 12 V 2 m −2 Hz −1 parallel to the surface and 3×10 −12 V 2 m −2 Hz −1 normal to the surface.…”
Section: Native Oxidesmentioning
confidence: 99%
“…Using amorphous NbO 2 thin films, monostable switching devices have also been prepared. Nb 2 O 5 exhibits a high dielectric constant and electrochromism. Nb 2 O 5 is an excellent catalyst for the polymerization of propylene, dehydration of 2-butanol, and butene isomerization. , Nb 2 O 5 deposited on Pt foil can function as a thin film capacitor …”
Section: Introductionmentioning
confidence: 99%
“…11,12 Nb 2 O 5 deposited on Pt foil can function as a thin film capacitor. 13 The phase diagram of the Nb-O system compiled by Massalski et al 14 shows NbO, NbO 2 , and Nb 2 O 5 as the only stable oxide phases. More recent research on phase equilibria in the system Nb-O [15][16][17][18][19] has revealed the existence of several other oxide phases.…”
Section: Introductionmentioning
confidence: 99%
“…Breakdown strengths of the order of 1 • 106 Vcm -1 for ion-cathode grown films on Ta may be compared with the breakdown strengths of tantalum oxide films obtained by aqueous methods (14) and by usual plasma techniques (6,13,14). The breakdown strengths of vapor-anodized niobium oxide films are also comparable (17). The breakdown voltages in a forward (metal positive) direction for oxide films grown on Zr, Ti, W, and V metals are 111, 83, 66, and 31V, respectively.…”
Section: Resultsmentioning
confidence: 99%